2010
DOI: 10.1111/j.1365-2427.2010.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater rock pools: a review of habitat characteristics, faunal diversity and conservation value

Abstract: SUMMARY1. In the light of the recent surge of interest in small and often temporary wetlands as model systems for ecological and evolutionary research, this article reviews current knowledge on freshwater rock pools and their fauna. 2. Freshwater rock pools occur all over the globe in all major biomes and depend mainly on precipitation for filling. Rock pool clusters are some of the more persistent and oldest freshwater habitats worldwide. Interactions between climate and geology (e.g. limestone, sandstone, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
151
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(156 citation statements)
references
References 114 publications
3
151
2
Order By: Relevance
“…surface area, volume, degree of connection with adjacent running channels, presence of marginal vegetation, quantity of periphyton and fish biomass). Particularly in case of freshwater rock pools the highly variable environmental conditions in such small restricted water volumes, in addition to exposition of seasonal an erratic weather, require high stress tolerance of the biota, with adaptations for surviving the dry phase such as the production of resistant stages and active emigration followed by quick re-colonization (Jocque et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…surface area, volume, degree of connection with adjacent running channels, presence of marginal vegetation, quantity of periphyton and fish biomass). Particularly in case of freshwater rock pools the highly variable environmental conditions in such small restricted water volumes, in addition to exposition of seasonal an erratic weather, require high stress tolerance of the biota, with adaptations for surviving the dry phase such as the production of resistant stages and active emigration followed by quick re-colonization (Jocque et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has previously been shown that similar 'mild' salinity differences can affect microbial communities both in terms of function and composition (for example, Langenheder et al, 2003). Another possibility could therefore be that the rock pool communities were already 'pre-conditioned' to environmental fluctuations, as they regularly experience quite drastic differences in environmental conditions (Jocque et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some parts of the Western Ghats of Maharashtra possess unique and interesting habitats in the form of rocky outcrops (Widdowson and Cox, 1996;Jog et al, 2002) which are generally known to host rich large branchiopod fauna (Pinder et al, 2000;Timms 2006;Brendonck et al, 2010;Jocque et al, 2010). Despite these facts, ecological and distributional studies on the large branchiopod in these parts of Ghats and surrounding areas are rare to the best of our knowledge, with only a few published reports (Pai, 1958;Karande and Inamdar, 1959, 1960, 1964Padhye et al, 2011aPadhye et al, , 2011bPadhye et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%